Mammary Tumors in Dogs, Recent Perspectives and Antiangiogenesis as a Therapeutic Strategy: Literature Study - Sewoyo, Palagan Senopati; Adi, Anak Agung Ayu Mirah; Winaya, Ida Bagus Oka; Wirata, I Wayan (Jurnal Medik Veteriner, 2023)
A particular type of tumor that is frequently detected in female dogs who are sexually active is a mammary tumor. Neoplasia results from DNA-based alterations in cell cycle regulating genes. The mammary gland is prone to the formation of tumors due to its dynamic structure. The development of this tumor is supported by numerous variables. It has been recently discovered that there is substantial evidence linking the BRCA2 gene to the process of cancer. Standard examination techniques, such as fine needle aspiration, histopathology, and immunohistochemistry, are used along with ancillary tests to determine the tumor type and degree of malignancy. The primary treatment option for malignant tumors is surgical resection followed by adjuvant chemotherapy; benign tumors necessitate surgical resection as well. Adjuvant therapy options include hormone therapy and non-steroidal anti-inflammatory medications. Tumor tissue undergoes angiogenesis as it grows and develops to accommodate the abundant supply of nutrients. Therefore, angiogenesis-inhibiting therapies can be utilized to halt the growth of tumor cells. A number of antiangiogenic medications are now being studied in clinical settings on humans, and several more are undergoing trials on animals. In addition to pharmaceuticals, viruses may be used as a therapeutic to block tumor angiogenesis.